The fertilizer norms to get higher effectiveness from vegetables - M.A Khayitov; M.I Mashrabov; N. Esirgapov (Proceedings of The ICECRS, 2019)
The purpose of this article was to determine the effectiveness of phosphorus fertilizers in vegetable and potato crop rotation. Provides high and high yields with the use of 100 - 140 kg / ha of phosphorus fertilizers on the background of N200K90 in vegetable growing. The NKFU's reliably complementary crop, used as phosphorus fertilizer, is about 140 kg / ha in the onion crop, although it is consumed at the rate of R2O5 per hectare in white cabbage, potatoes and sweet peppers.